THE EFFECT OF CAPITAL STRUCTURE, SYSTEMATIC RISK, AND UNSYSTEMATIC RISK ON STOCK RETURN - Nera Marinda Machdar (Business and Entrepreneurial Review, 2015)
The purpose of study was to analyze the effect of capital structure, systematic risk on stock return. The model proposed was evaluated using SPSS statistics 22. Samples in this study are public firms listed on the Indonesian stock Exchange with LQ 45 Index for period 2009-2012. The result of this study showed that (1) The variable of capital structure, systematic risk and unsytematic risk together have a positive influence on stock return; (2) The capital structure has a positive and significant impact on stock return; (3) The systematic risk (beta) has a negative effect on stock return; and (4) The unsystematic risk has a negative effect on stock return. The limitations of this study were as follows: (1) The number of sample used in this study is small, so the result might not be able to describe the overall companies; (2) The study was only investigated the sample firm from manufacturing sector with LQ45 Index; (3) The study calculated stock returns without considering the risks. Therefore, it was necessary to manner. Subsequent research suggested that (1) The number of samples shoulds be increased; (2) The sample of companies in the industry should be expanded; (3) The stock return by calculating the risk adjusted return should be considered.